Impact of Anti–PD-1 and Anti–CTLA-4 on the Human Immunodeficiency Virus (HIV) Reservoir in People Living With HIV With Cancer on Antiretroviral Therapy: The AIDS Malignancy Consortium 095 Study. (2nd March 2021) - Rasmussen, Thomas A; Rajdev, Lakshmi; Rhodes, Ajantha; Dantanarayana, Ashanti; Tennakoon, Surekha; Chea, Socheata; Spelman, Tim; Lensing, Shelly; Rutishauser, Rachel; Bakkour, Sonia; Busch, Michael; Siliciano, Janet D; et al.
Abstract: Background: Antibodies to programmed cell death 1 (PD-1) and cytotoxic T-lymphocyte–associated protein 4 (CTLA-4) may perturb human immunodeficiency virus (HIV) persistence during antiretroviral therapy (ART) by reversing HIV latency and/or boosting HIV-specific immunity, leading to clearance of infected cells. We tested this hypothesis in a clinical trial of anti–PD-1 alone or in combination with anti–CTLA-4 in people living with HIV (PLWH) and cancer. Methods: This was a substudy of the AIDS Malignancy Consortium 095 Study. ART-suppressed PLWH with advanced malignancies were assigned to nivolumab (anti–PD-1) with or without ipilimumab (anti–CTLA-4). In samples obtained preinfusion and 1 and 7 days after the first and fourth doses of immune checkpoint blockade (ICB), we quantified cell-associated unspliced (CA-US) HIV RNA and HIV DNA. Plasma HIV RNA was quantified during the first treatment cycle. Quantitative viral outgrowth assay (QVOA) to estimate the frequency of replication-competent HIV was performed before and after ICB for participants with samples available. Results: Of 40 participants, 33 received nivolumab and 7 nivolumab plus ipilimumab. Whereas CA-US HIV RNA did not change with nivolumab monotherapy, we detected a median 1.44-fold increase (interquartile range, 1.16–1.89) after the first dose of nivolumab and ipilimumab combination therapy ( P = .031). There was no decrease in the frequency of cells containing replication-competent HIV, but in the 2 individuals on combination ICB for whom we had longitudinal QVOA, we detected decreases of 97% and 64% compared to baseline. Conclusions: Anti–PD-1 alone showed no effect on HIV latency or the latent HIV reservoir, but the combination of anti–PD-1 and anti–CTL-4 induced a modest increase in CA-US HIV RNA and may potentially eliminate cells containing replication-competent HIV. Clinical Trials Registration: NCT02408861. Abstract : In people living with human immunodeficiency virus (HIV) on antiretroviral therapy receiving immune checkpoint blockade for cancer, anti–PD-1 alone had no effect on the latent HIV reservoir, but the combination of anti–PD-1 and anti–CTLA-4 modestly reversed HIV latency and may potentially eliminate cells containing replication-competent HIV.